Філогенез та систематичне положення роду Rhamnus L. - Zhurzha, Yu.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to generalize data on the phylogenetic formation and systematic position of the genus Rhamnus L. Material and methods. The study of the systematic position of the family Rhamnaceae and the genus Rhamnus was conducted by scientists on the basis of comparative morphology, anatomy, biochemistry, embryology and molecular data. Results. Based on the analysis of paleobotanical data, the distribution of the genus Rhamnus in the previous geological epochs has been elucidated. The history of the study of taxonomy of the genus Rhamnus is considered. The chronology and dynamics of changes in the systematic position of the genus Rhamnus have been established throughout the history of his research. Detailed studies in this direction have been carried out since the second half of the XIX century and are continuing at the present time. The site of the genus Rhamnus is studied in modern phylogenetic systems. Synonymy of species names of representatives of the genus Rhamnus has been studied. Conclusion. Based on results of phylogenetic studies confirmed by genetic tests, it was found that the genus Rhamnus enters the tribe Rhamneae, the family Rhamnaceae, of the order of Rosales.